One piece. Collection no. 25 [videorecording (DVD)] - Oda, Eiichirō, 1975- (Funimation, 2021)
The lab children are suffering withdrawals, and the man responsible happens to be Law's next target. A Straw Hat and Heart Pirate alliance is in order! But their gaseous nemesis sets a slime monster hot on their trails, chasing the Straw Hats into the lab. Children rampage for candy, Monet chills Luffy to the core, and as the poison gas creeps closer, an unlikely hero could tip the scales.